Application of Motivation and Development to the Performance of Coffeeshop Alco Discussion House to Realize an Organizational Culture that is Aligned with Organizational Goals - Afhal Rahmat Kholid; Marta Widian Sari; Dinal Adriansyah; Irfandi Saputra (LPPM UIKA Bogor, 2023)
This study aims to examine the application of work motivation, and performance development in realizing the best organizational culture at the UMKM coffee shop discussion house alco, Jl Durian. Tarung, Kec. Kuranji, Padang city, West Sumatra. Data collection techniques in this study were questionnaires and interviews. The results showed that rewards and work ethics have a significant effect on employee motivation. The results of this study indicate that there is a significant influence of the reward system on employee motivation. This can be seen where employees who are given appreciation or rewards show better performance than employees who are not given rewards. So it can be concluded that the reward system for employees has a positive effect on employee motivation to achieve organizational culture.